1997
DOI: 10.1038/sj.ejcn.1600362
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of bone mineralization in 8 to 20 year old Finnish females

Abstract: Objectives:To study the determinants of bone mass and density in Finnish girls and young women. Design: A cross-sectional study. Subjects: One hundred and seventy six 8 to 20 year old female volunteers living in the city of Tampere, Finland. Methods: Calcium intake was estimated from a 7 d calcium intake diary (CaD). Bone mineral content (BMC) and areal density (BMD) were measured by dual-energy X-ray absorptiometry (DXA) at the lumbar spine, femoral neck and distal radius. Volumetric bone mineral apparent den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 24 publications
1
23
0
2
Order By: Relevance
“…Cross-sectional studies have shown conflicting results. Some studies found a positive association between calcium intake and BMD or BMC [5,6], but in most there was no relation between bone mass and calcium intake [7][8][9][10]14]. In a new crosssectional study with girls aged 11-15 years including data from six European countries there was no relation between calcium intake and radial BMD [11].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Cross-sectional studies have shown conflicting results. Some studies found a positive association between calcium intake and BMD or BMC [5,6], but in most there was no relation between bone mass and calcium intake [7][8][9][10]14]. In a new crosssectional study with girls aged 11-15 years including data from six European countries there was no relation between calcium intake and radial BMD [11].…”
Section: Discussionmentioning
confidence: 89%
“…However, the role of calcium intake in bone mineralization during growth is still controversial because of conflicting results from observational and intervention studies [5][6][7][8][9][10][11]. Furthermore, the close relation between areal bone mineral density (BMD), bone mineral content (BMC) and body size may lead to size-related artifacts in comparisons with variables that are themselves size-related, such as dietary intake and muscle strength [12,13].…”
Section: Introductionmentioning
confidence: 98%
“…Mechanical loading has been said to have the greatest influence on the skeleton during growth [1,3,9], the body weight and lean body mass being the most important determinants of the bone mass at that phase [7,10,11]. Kannus et al [1] showed in a crosssectional study of female tennis and squash players that the benefit of mechanical loading on the bone mass of the playing arm was about 2 times greater if women started the playing at or before menarche rather than after it.…”
Section: Introductionmentioning
confidence: 97%
“…Excercise may increase volumetric bone mineral apparent density. Observations of Uusi-Rasi et al (1997) in Finnish females between 8 and 20 y show that physical activity produces 5 ± 7% bene®ts in bone mineral variables, and in Chinese adolescents physical ®tness was a signi®cant positive predictor of bone mineral density of the L2 ± L4 vertebrae (Cheng et al, 1998).…”
Section: S3mentioning
confidence: 99%